Xylem water potentials of native shrubs from northeastern Mexico - González Rodríguez, Humberto; Cantú Silva, Israel; Ramírez Lozano, Roque Gonzalo; Gómez Meza, Marco Vinicio; Sarquís Ramírez, Jorge I.; Coria Gil, Norma A.; Cervantes Montoya, M. V.; Maiti, Ratikanta (Almquist & Wilkesells, 2011)
Xylem water potentials (C) were evaluated in browse plants such as Forestiera angustifolia (Oleaceae), Celtis pallida (Ulmaceae), Zanthoxylum fagara (Rutaceae), and Eysenhardtia texana (Fabaceae). Collections were carried out at Linares County, a semi-arid region of northeastern Mexico. C (MPa) were estimated at 10-day intervals between July 10 and September 30, 2008 by using a Scholander pressure bomb, and were monitored in five different plants per species at 06:00 h (predawn) and 14:00 h (midday). Air temperature, relative humidity, precipitation, and soil water content were registered throughout. Data were subjected to one-way ANOVA and linear correlation analysis. At the wettest period, C at predawn varied from 0.29 (C. pallida and E. texana) to 0.37 (F. angustifolia and Z. fagara); in contrast, at the driest period, predawn C ranged from 3.28 (F. angustifolia) to 4.50 (Z. fagara). At midday E. texana achieved the highest (1.14) and lowest (4.20) values at wettest and driest sampling dates, respectively. It seems that air temperature and vapor pressure deficit negatively influenced C values in all species; conversely, C values augmented as relative humidity increased. Since F. angustifolia and C. pallida maintained higher predawn and midday C values under water stress, these species may be considered as drought-adapted species while, Z. fagara and E. texana that acquired lower values, may be less adapted to drought and in physiological disadvantage under limited water conditions.